Extracting cacao [sic] beans, Trinidad - (:unkn) unknown (My University, 2010)
A picture of a group of labourers gathered around a large pile of cocoa pods with some sitting and breaking the pods to get the beans. A description on the back of the postcard reads, "After being picked the Cacao [sic] pods are put into heaps in the field where the beans are extracted. They are then sent to the fermentation houses and are subsequently dried." Postcard B2.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Working class--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; Agricultural laborers--Trinidad and Tobago; Plantation workers--Trinidad and Tobago